The Use of Multiband PSS to Improve Transient Stability of Multimachine Power System - Nacim Cherif; Allaoui Tayeb; Benasla Mokhtar (Institute of Advanced Engineering and Science, 2013)
With the increase in demand for electrical energy, electrical networks must constantly work near their stability limits faster and more flexible. These grids are often subject to disturbances such as short circuits which cause the loss of stability of generators and the entire network. In this work we present two different approaches to PSS (power system stabilizer), the conventional PSS and multiband PSS in order to improve transient stability of multimachine network. The latter is subjected to a short-circuit current with a duration of 200ms just 350 km from the first generator. Multiband PSS offers an additional advantage since it produces a signal stabilizing not only from the variation of the angular velocity of the rotor as well as electrical power. Instead of one, it uses three filters (Lead/Lag) independent, each optimized for vibration damping local oscillations between interconnected networks and global oscillations. Different simulations were performed using the software matlab sympower system.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.3905